Preparation method of fuel cell membrane electrode based on multi-scale carbon nanotubes
Through the treatment and mixing technology of multi-scale carbon nanotubes, the insufficient conductivity and agglomeration of the catalytic layer of the fuel cell membrane electrode are solved, and more efficient electrochemical reactions and more stable membrane electrode performance are achieved.
Patent Information
- Application Number
- CN202411185020.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-27
AI Technical Summary
In the prior art, the electrical conductivity of the fuel cell membrane electrode catalytic layer is poor, resulting in hindered charge transfer, affecting the electrochemical reaction rate and efficiency, and carbon nanotubes with a single aspect ratio are prone to agglomeration, reducing the performance and stability of the catalytic layer. .
Using multi-scale carbon nanotubes, large-dimensional and small-dimensional carbon nanotube slurry is prepared by sonication and ball milling, and mixed with Pt/C catalyst to form a uniform catalytic layer slurry, which is then used to spray and The film electrode is prepared by hot pressing technology to ensure the continuity of the conductive pathway and the uniform dispersion of components.
The conductivity and utilization of the catalytic layer are improved, agglomeration is avoided, the stability and durability of the membrane electrode are enhanced, and it is suitable for large-scale production.
Smart Images

Figure CN119208626A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of membrane electrode technology, and in particular to a method for preparing a fuel cell membrane electrode based on multi-scale carbon nanotubes. Background Art
[0002] As energy crisis and environmental problems become increasingly serious, fuel cells, as an efficient and clean energy conversion device, have received widespread attention. The fuel cell membrane electrode assembly (MEA) is the core component of the fuel cell, and its performance directly affects the overall performance of the fuel cell. In the MEA, the catalyst layer is the main site of the electrochemical reaction, so the performance of the catalyst layer is crucial to the performance of the fuel cell.
[0003] As the active area of the electrochemical reaction, the fuel cell catalyst layer needs to effectively transfer electrons and ions to ensure the efficient electrochemical reaction. If the conductivity of the catalyst layer is poor, the charge transfer will be blocked, which will affect the rate and efficiency of the electrochemical reaction and reduce the output power of the fuel cell.
[0004] As a one-dimensional nanomaterial with excellent electrical conductivity and mechanical properties, carbon nanotubes have higher electrical conductivity and larger specific surface area, which can effectively improve the conductivity and reaction activity of the catalyst layer. By adding carbon nanotubes to the catalyst layer of the fuel cell, they can be used together with the Pt / C catalyst to form a more efficient electrochemical reaction interface, ensure the rapid transmission of electrons in the catalyst layer, and reduce the resistance of charge transmission. At the same time, the large specific surface area of carbon nanotubes can increase the contact area between the catalyst layer and the reaction gas, improve the reaction activity, and further enhance the performance of the fuel cell.
[0005] For example, in the prior art, a method for preparing a catalyst layer for a proton exchange membrane fuel cell is provided in a patent document with publication number CN103401000B, by spraying a first material (activated carbon), a second material (carbon nanotubes) and a third material (helical carbon nanotubes) on an electrode to form a catalyst layer. A patent document with publication number CN108878898B discloses a fuel cell with a separated electrolyte distribution and a method for manufacturing the same. By using a combination of carbon nanotubes and ionomers, and combining specific manufacturing steps, a structure with a separated electrolyte distribution in a fuel cell is achieved, which helps to improve the performance and efficiency of the fuel cell, and may also improve its stability and durability. A patent document with publication number CN113078338B provides an optimized fuel cell membrane electrode and a method for preparing the same. By accurately mixing Pt / C catalyst, graphitized multi-walled carbon nanotubes and perfluorosulfonic acid resin solution, an optimized cathode catalyst layer slurry is prepared, which effectively improves the problem of catalyst carrier shedding and platinum migration, and improves the durability and stability of the fuel cell.
[0006] However, the prior art does not optimize the aspect ratio of carbon nanotubes. When only carbon nanotubes with a single aspect ratio are mixed with Pt / C catalysts, the conductive pathways in the catalytic layer are often not continuous and uniform enough, which will lead to local concentration of electrochemical reactions and reduce the utilization and stability of the catalytic layer. In addition, carbon nanotubes with a single aspect ratio are prone to form agglomerates in the catalytic layer, further reducing the performance of the catalytic layer. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing a fuel cell membrane electrode based on multi-scale carbon nanotubes to solve the following technical problems:
[0008] How to improve the performance of the catalyst layer in fuel cell membrane electrode?
[0009] The purpose of the present invention can be achieved through the following technical solutions:
[0010] A method for preparing a fuel cell membrane electrode based on multi-scale carbon nanotubes comprises the following preparation steps:
[0011] S1: ultrasonically treating a large aspect ratio carbon nanotube (L-CNTs) solution in a water bath to obtain an L-CNTs slurry; placing a small aspect ratio carbon nanotube (S-CNTs) solution in a ball mill for ball milling to obtain an S-CNTs slurry; shearing, dispersing, and cooling a Pt / C catalyst solution to obtain a Pt / C catalyst slurry.
[0012] S2: mixing L-CNTs slurry, S-CNTs slurry, Pt / C catalyst slurry and stabilizer to obtain a mixed slurry; the mass ratio of the total mass of L-CNTs slurry and S-CNTs slurry to the mass ratio of Pt / C catalyst slurry is (1-4):10, wherein the mass ratio of L-CNTs slurry to S-CNTs slurry is 1:(1-5);
[0013] Preferably, the stabilizer is a Nafion solution with a mass fraction of 4%-6%;
[0014] More preferably, the mass fraction of the Nafion solution is 5%.
[0015] S3: Ultrasonic spraying of the mixed slurry, adjusting the nozzle movement speed and the discharge speed, and controlling the anode platinum loading to 0.05-0.15 mg / cm 2 , the cathode platinum loading is 0.3-0.4 mg / cm 2 , obtaining an anode catalyst layer and a cathode catalyst layer.
[0016] S4: stacking gas diffusion layers on the anode catalyst layer and the cathode catalyst layer respectively, and then hot pressing to finally obtain a fuel cell membrane electrode based on multi-scale carbon nanotubes.
[0017] In a further embodiment of the present invention: in step S1, the method of ultrasonically treating the L-CNTs solution under water bath conditions is as follows: dissolving the L-CNTs in a certain amount of deionized water and mixing them uniformly to form a L-CNTs solution with a mass fraction of 1.5%-2.5%, ultrasonically treating the L-CNTs solution at a water bath temperature of 8-12° C., gradually reducing the ultrasonic power from 500 W to 100 W, and the ultrasonic treatment time is 45-75 min;
[0018] Among them, the diameter of L-CNTs is 10-20nm and the length is 5-30um;
[0019] Preferably, the mass fraction of the L-CNTs solution is 2%;
[0020] Preferably, the water bath temperature is 10°C;
[0021] Preferably, the ultrasonic treatment time is 60 min.
[0022] In a further embodiment of the present invention, the specific steps of gradually reducing the ultrasonic power from 500 W to 100 W are: firstly ultrasonically treating at 500 W for 15-25 min, then ultrasonically treating at 250-350 W for 15-25 min, and finally ultrasonically treating at 100 W for 15-25 min;
[0023] Preferably, the duration of each ultrasonic treatment is 20 min.
[0024] In a further embodiment of the present invention, in step S1, a method for placing a small aspect ratio carbon nanotube (S-CNTs) solution in a ball mill for ball milling is as follows: S-CNTs are dissolved in a certain amount of deionized water and mixed evenly to form a S-CNTs solution with a mass fraction of 1.5%-2.5%; the S-CNTs solution is placed in a ball milling jar, wherein the ball milling medium in the ball milling jar is ZrO2 with a particle size between 1.0 and 1.2 mm, and the ball-to-material ratio is (15-20):1; ball milling is performed at 200-300 r / min for 110-130 min at 8-12°C;
[0025] Among them, the diameter of S-CNTs is 10-20nm and the length is 1-5um;
[0026] Preferably, the mass fraction of the S-CNTs solution is 2%;
[0027] Preferably, the ball-to-material ratio is 18:1;
[0028] Preferably, the ball milling temperature is 10°C;
[0029] Preferably, the ball milling rate is 250 r / min and the ball milling time is 120 min.
[0030] In a further embodiment of the present invention: in step S1, the method of shearing, dispersing and cooling the Pt / C catalyst solution is: dissolving the Pt / C catalyst in a certain amount of deionized water and mixing evenly to obtain a Pt / C catalyst solution with a mass fraction of 1.5%-2.5%; shearing the Pt / C catalyst at 4500-5500 rpm at 8-12° C. for 25-35 min, and then transferring it to a high-pressure homogenizer for dispersion;
[0031] Wherein, the platinum content in the Pt / C catalyst is 20%-60%;
[0032] Preferably, the platinum content in the Pt / C catalyst is 40%
[0033] Preferably, the mass fraction of the Pt / C catalyst solution is 2%;
[0034] Preferably, the shear temperature is 10%;
[0035] Preferably, the shear rate is 5000 rpm and the shear time is 30 min;
[0036] In a further embodiment of the present invention, the specific steps of transferring to a high pressure homogenizer for dispersion are:
[0037] First, homogenize two processes at 45-55MPa, then increase the pressure to 65-75MPa to homogenize one process, and finally reduce the pressure to 35-45MPa to homogenize one process; the valve body temperature of the high-pressure homogenizer is 8-12℃;
[0038] Preferably, first homogenize two processes at 50 MPa, then increase the pressure to 70 MPa to homogenize one process, and finally reduce the pressure to 40 MPa to homogenize one process;
[0039] Preferably, the valve body temperature of the high-pressure homogenizer is controlled to 10° C. by circulating cooling water.
[0040] In a further embodiment of the present invention: in step S2, the ratio of the dry weight of the stabilizer to the total weight of L-CNTs, S-CNTs and Pt / C catalyst (total dry weight of carbon substances) is (0.7-0.9):1;
[0041] Preferably, the ratio of the dry weight of the stabilizer to the total dry weight of the carbon material is 0.8:1.
[0042] In a further embodiment of the present invention: in step S2, the specific method of mixing the L-CNTs slurry, the S-CNTs slurry, the Pt / C catalyst slurry, and the stabilizer is: ultrasonically mixing the four at 150-250W for 10-20min at 8-12°C, and then shearing at 4500-5500rpm for 25-35min;
[0043] Preferably, the temperature of ultrasonic mixing is 10 min;
[0044] Preferably, the power of ultrasonic mixing is 200W, and the time of ultrasonic mixing is 15min;
[0045] Preferably, the shear rate is 5000 rpm and the shear time is 30 min.
[0046] In a further embodiment of the present invention: in step S3, the temperature of the stage carrying the proton membrane is 80-90°C;
[0047] Preferably, the stage temperature is 85°C.
[0048] In a further embodiment of the present invention: in step S4, the thickness of the gas diffusion layer is 215-225 um;
[0049] Preferably, the thickness of the gas diffusion layer is 220 um;
[0050] In a further embodiment of the present invention, in step S4, the method of hot pressing is: placing the cathode catalyst layer and the anode catalyst layer after the gas diffusion layer is stacked into a mold of a hot press, and hot pressing them at 130-150° C. and 2-4 MPa for 1.5-2.5 min;
[0051] Preferably, the hot pressing temperature is 140°C;
[0052] Preferably, the hot pressing pressure is 3MPa;
[0053] Preferably, the hot pressing time is 2 minutes.
[0054] Beneficial effects of the present invention:
[0055] In the preparation method of the fuel cell membrane electrode based on multi-scale carbon nanotubes of the present invention, large aspect ratio carbon nanotubes, small aspect ratio carbon nanotubes and Pt / C catalyst slurry are dispersed separately and then mixed to achieve uniform dispersion of the components in the catalyst layer slurry, fully utilize the advantages of carbon nanotubes with different aspect ratios, form a continuous and uniform conductive path, thereby improving the conductivity and utilization rate of the catalyst layer; the method of separately dispersing and mixing the three slurries can optimize the dispersibility of the components in the catalyst layer, avoid the occurrence of agglomeration, and improve the stability and durability of the catalyst layer; at the same time, the method is simple and easy to implement, and multi-walled carbon nanotubes with different aspect ratios can be directly obtained through commercial channels, so it is suitable for large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] The present invention will be further described below in conjunction with the accompanying drawings.
[0057] Figure 1 It is a flow chart of the method for preparing a fuel cell membrane electrode based on multi-scale carbon nanotubes of the present invention;
[0058] Figure 2 is a comparison diagram of polarization curves of membrane electrodes prepared in Examples 1-4 of the present invention;
[0059] Figure 3 It is a comparison diagram of the electrochemical impedance of the membrane electrodes prepared in Examples 1-4 of the present invention. DETAILED DESCRIPTION
[0060] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0061] See also Figure 1 The present invention is a method for preparing a fuel cell membrane electrode based on multi-scale carbon nanotubes, comprising the following preparation steps:
[0062] Step 1: subjecting the L-CNTs solution to ultrasonic treatment in a water bath to obtain L-CNTs slurry; subjecting the S-CNTs solution to ball milling treatment in a ball mill to obtain S-CNTs slurry; and subjecting the Pt / C catalyst solution to shearing, dispersing, and cooling to obtain Pt / C catalyst slurry;
[0063] Specifically:
[0064] (1) The method of ultrasonically treating the L-CNTs solution under water bath conditions is as follows: preparing L-CNTs with a diameter of 10-20 nm and a length of 5-30 μm, dissolving the L-CNTs in a certain amount of deionized water and mixing them evenly to form an L-CNTs solution with a mass fraction of 1.5%-2.5%, and ultrasonically treating the L-CNTs solution at a water bath temperature of 8-12° C., gradually reducing the ultrasonic power from 500 W to 100 W, and the ultrasonic treatment time is 45-75 min;
[0065] For example, first ultrasonically treat at 500 W for 15-25 min, then ultrasonically treat at 250-350 W for 15-25 min, and finally ultrasonically treat at 100 W for 15-25 min;
[0066] (2) The method of placing a small aspect ratio carbon nanotube (S-CNTs) solution in a ball mill for ball milling is as follows: prepare S-CNTs with a diameter of 10-20 nm and a length of 1-5 μm, dissolve the S-CNTs in a certain amount of deionized water and mix them evenly to form a S-CNTs solution with a mass fraction of 1.5%-2.5%; place the S-CNTs solution in a ball mill, wherein the ball milling medium in the ball mill is ZrO2 with a particle size of 1.0-1.2 mm, and the ball-to-material ratio is (15-20):1; ball milling is performed at 200-300 r / min at 8-12°C for 110-130 min;
[0067] (3) The method for shearing, dispersing and cooling the Pt / C catalyst solution is as follows: preparing a Pt / C catalyst with a platinum content of 20% to 60%, dissolving the Pt / C catalyst in a certain amount of deionized water and mixing evenly to obtain a Pt / C catalyst solution with a mass fraction of 1.5% to 2.5%; shearing the Pt / C catalyst at 4500 to 5500 rpm at 8 to 12° C. for 25 to 35 minutes, and then transferring it to a high-pressure homogenizer for dispersion;
[0068] For example, first homogenize two processes at 45-55MPa, then increase the pressure to 65-75MPa to homogenize one process, and finally reduce the pressure to 35-45MPa to homogenize one process; the valve body temperature of the high-pressure homogenizer is 8-12℃.
[0069] Step 2: mixing L-CNTs slurry, S-CNTs slurry, Pt / C catalyst slurry and stabilizer to obtain a mixed slurry; the mass ratio of the total mass of L-CNTs slurry and S-CNTs slurry to the mass ratio of Pt / C catalyst slurry is (1-4):10, wherein the mass ratio of L-CNTs slurry to S-CNTs slurry is 1:(1-5);
[0070] The stabilizer can be a Nafion solution with a mass fraction of 4%-6%. At the same time, the ratio of the dry weight of the stabilizer to the total mass of L-CNTs, S-CNTs, and Pt / C catalyst (total dry weight of carbon substances) is (0.7-0.9):1;
[0071] Specifically:
[0072] The specific method of mixing L-CNTs slurry, S-CNTs slurry, Pt / C catalyst slurry and stabilizer is: ultrasonically mix the four at 150-250W for 10-20 minutes at 8-12°C, and then shear at 4500-5500rpm for 25-35 minutes.
[0073] Step 3: Ultrasonic spray the mixed slurry, adjust the nozzle movement speed and discharge speed, and control the anode platinum loading to 0.05-0.15 mg / cm 2 , the cathode platinum loading is 0.3-0.4 mg / cm 2 , obtaining an anode catalyst layer and a cathode catalyst layer;
[0074] Among them, the temperature of the carrier supporting the proton membrane is 80-90°C.
[0075] Step 4: stacking gas diffusion layers on the anode catalyst layer and the cathode catalyst layer respectively, and then hot pressing to finally obtain a fuel cell membrane electrode based on multi-scale carbon nanotubes;
[0076] Among them, the thickness of the gas diffusion layer is 215-225um;
[0077] Specifically:
[0078] The method for hot pressing is: putting the cathode catalyst layer and the anode catalyst layer after stacking the gas diffusion layer into the mold of the hot press machine, and hot pressing them at 130-150° C. and 2-4 MPa pressure for 1.5-2.5 minutes.
[0079] Next, according to the preparation method of the fuel cell membrane electrode based on multi-scale carbon nanotubes of the present invention, a specific embodiment 1 is implemented, and comparative examples 1-4 are set according to embodiment 1 for relevant verification, wherein the relevant materials involved in embodiment 1 and comparative examples 1-4 are as follows:
[0080] (1) Prepare L-CNTs with a diameter of 10-20 nm and a length of 5-30 μm.
[0081] (2) Prepare S-CNTs with a diameter of 10-20 nm and a length of 1-5 μm.
[0082] (3) Prepare a Pt / C catalyst with an average particle size of 2-5 nm and a platinum content of 40%.
[0083] (4) Prepare a 5% Nafion solution.
[0084] Example 1
[0085] Step 1: Decentralize processing
[0086] (1) L-CNTs dispersion
[0087] L-CNTs were dissolved in a certain amount of deionized water and mixed evenly to form a 2% L-CNTs solution by mass. The L-CNTs solution was added to an ultrasonic water bath constant temperature oscillator, the water bath temperature was adjusted to 10°C, and the solution was first ultrasonically treated at 500W for 20min, then ultrasonically treated at 300W for 20min, and finally ultrasonically treated at 100W for 20min to obtain L-CNTs slurry.
[0088] (2) S-CNTs dispersion
[0089] The S-CNTs were dissolved in a certain amount of deionized water and mixed evenly to form a S-CNTs solution with a mass fraction of 2%. The S-CNTs solution was placed in a ball mill, wherein the ball milling medium in the ball mill was ZrO2 with a particle size between 1.0 and 1.2 mm, and the ball-to-material ratio was 18:1. The S-CNTs solution was ball milled at 250 r / min for 120 min at 10°C to obtain a S-CNTs slurry.
[0090] (3) Pt / C catalyst dispersion
[0091] The Pt / C catalyst was dissolved in a certain amount of deionized water and mixed evenly to obtain a Pt / C catalyst solution with a mass fraction of 2%. The Pt / C catalyst was placed in a shearing machine, sheared at 5000 rpm for 30 minutes at 10°C, and then transferred to a high-pressure homogenizer with a valve body temperature set at 10°C, first homogenized two processes at 50MPa, then increased the pressure to 70MPa to homogenize one process, and finally reduced the pressure to 40MPa to homogenize one process to obtain a Pt / C catalyst slurry.
[0092] Step 2: Slurry preparation
[0093] L-CNTs slurry, S-CNTs slurry, Pt / C catalyst slurry and Nafion solution were added to an ultrasonic mixer, the mass ratio of the total mass of L-CNTs slurry and S-CNTs slurry to the mass ratio of Pt / C catalyst slurry was 3:10, wherein the mass ratio of L-CNTs slurry to S-CNTs slurry was 1:3; the ratio of the dry weight of the Nafion solution to the total mass of L-CNTs, S-CNTs and Pt / C catalyst (total dry weight of carbon matter) was 0.8:1, the temperature of the ultrasonic mixer was set to 10°C, ultrasonic mixing was performed at 200W for 15 minutes, and then the mixture was transferred to a shear mixer and sheared at 5000rpm for 30 minutes to obtain a mixed slurry.
[0094] Step 3: Membrane Electrode Fabrication
[0095] Ultrasonic spraying was performed on the mixed slurry, and the nozzle movement speed and discharge speed were adjusted to control the anode platinum loading to 0.1 mg / cm 2 , the cathode platinum loading is 0.35 mg / cm 2 , obtaining an anode catalyst layer and a cathode catalyst layer; wherein, the platform temperature of the proton membrane is 85°C; subsequently, a 220um gas diffusion layer is stacked on the anode catalyst layer and the cathode catalyst layer respectively, and then loaded into a mold of a hot press, and hot-pressed at 140°C and 3MPa pressure for 2min to obtain a fuel cell membrane electrode based on multi-scale carbon nanotubes.
[0096] Comparative Example 1
[0097] Compared with Example 1, the only difference is that L-CNTs slurry and S-CNTs slurry are not added, and other conditions are the same.
[0098] The specific steps are as follows:
[0099] Step 1: Decentralize processing
[0100] This step is exactly the same as the step of dispersing the Pt / C catalyst slurry in Example 1.
[0101] Step 2: Slurry preparation
[0102] The Pt / C catalyst slurry and Nafion solution were added into an ultrasonic mixer, the ratio of the dry weight of the Nafion solution to the dry weight of the Pt / C catalyst was 0.8:1, the temperature of the ultrasonic mixer was set to 10°C, ultrasonic mixing was performed at 200W for 15 minutes, and then transferred to a shear mixer and sheared at 5000rpm for 30 minutes to obtain a mixed slurry.
[0103] Step 3: Membrane Electrode Fabrication
[0104] This step is exactly the same as the membrane electrode manufacturing step in Example 1.
[0105] Comparative Example 2
[0106] Compared with Example 1, the only difference is that L-CNTs slurry is not added, and other conditions are the same.
[0107] The specific steps are as follows:
[0108] Step 1: Decentralize processing
[0109] (1) S-CNTs dispersion
[0110] This step is exactly the same as the step of dispersing S-CNTs in Example 1.
[0111] (2) Pt / C catalyst dispersion
[0112] This step is exactly the same as the step of dispersing the Pt / C catalyst slurry in Example 1.
[0113] Step 2: Slurry preparation
[0114] S-CNTs slurry, Pt / C catalyst slurry and Nafion solution were added into an ultrasonic mixer, the mass ratio of S-CNTs slurry to Pt / C catalyst slurry was 3:10, the ratio of dry weight of Nafion solution to the total mass of S-CNTs and Pt / C catalyst (total dry weight of carbon matter) was 0.8:1, the temperature of the ultrasonic mixer was set to 10°C, ultrasonic mixing was performed at 200W for 15min, and then the mixture was transferred to a shear mixer and sheared at 5000rpm for 30min to obtain a mixed slurry.
[0115] Step 3: Membrane Electrode Fabrication
[0116] This step is exactly the same as the membrane electrode manufacturing step in Example 1.
[0117] Comparative Example 3
[0118] Compared with Example 1, the only difference is that no S-CNTs slurry is added, and other conditions are the same.
[0119] The specific steps are as follows:
[0120] Step 1: Decentralize processing
[0121] (1) L-CNTs dispersion
[0122] This step is exactly the same as the step of dispersing L-CNTs in Example 1.
[0123] (2) Pt / C catalyst dispersion
[0124] This step is exactly the same as the step of dispersing the Pt / C catalyst slurry in Example 1.
[0125] Step 2: Slurry preparation
[0126] L-CNTs slurry, Pt / C catalyst slurry and Nafion solution were added into an ultrasonic mixer, the mass ratio of L-CNTs slurry to Pt / C catalyst slurry was 3:10, the ratio of dry weight of Nafion solution to the total mass of L-CNTs and Pt / C catalyst (total dry weight of carbon matter) was 0.8:1, the temperature of the ultrasonic mixer was set to 10°C, ultrasonic mixing was performed at 200W for 15min, and then the mixture was transferred to a shear mixer and sheared at 5000rpm for 30min to obtain a mixed slurry.
[0127] Step 3: Membrane Electrode Fabrication
[0128] This step is exactly the same as the membrane electrode manufacturing step in Example 1.
[0129] Comparative Example 4
[0130] Compared with Example 1, the only difference is that the dispersion of L-CNTs, S-CNTs and Pt / C catalyst is changed from step-by-step dispersion to synchronous dispersion, and the other conditions are exactly the same.
[0131] The specific steps are as follows:
[0132] Step 1: Decentralize processing
[0133] L-CNTs, S-CNTs, and Pt / C catalyst were added into quantitative deionized water, wherein the mass ratio of the total mass of L-CNTs and S-CNTs to the mass ratio of Pt / C catalyst was 3:10, and the mass ratio of L-CNTs to S-CNTs was 1:3. After being evenly mixed, a mixed solution with a mass concentration of 2% was obtained. The mixed solution was transferred to a shearing machine, sheared at 5000 rpm for 30 minutes at 10°C, and then transferred to a high-pressure homogenizer with a valve body temperature set at 10°C, first homogenized two processes at 50MPa, then increased the pressure to 70MPa to homogenize one process, and finally reduced the pressure to 40MPa to homogenize one process;
[0134] Step 2: Slurry preparation
[0135] Nafion solution was added to the cooled mixed solution, the ratio of the dry weight of the Nafion solution to the total mass of L-CNTs, S-CNTs and Pt / C catalyst (total dry weight of carbon matter) was 0.8:1, the temperature of the ultrasonic mixer was set to 10°C, ultrasonic mixing was performed at 200W for 15 minutes, and then transferred to a shear mixer and sheared at 5000rpm for 30 minutes to obtain a mixed slurry.
[0136] Step 3: Membrane Electrode Fabrication
[0137] This step is exactly the same as the membrane electrode manufacturing step in Example 1.
[0138] Next, the performance of the membrane electrodes prepared in Example 1 and Comparative Examples 1-4 was tested respectively, and the testing method was as follows:
[0139] The electrical properties of the membrane electrode are tested using a fuel cell test system. The reactants used in the system are compressed air and high-purity hydrogen. The system is equipped with an external humidification system. Different gas humidification effects are obtained by controlling the humidifier temperature. The specific test steps are as follows:
[0140] Before the test, the MEA is activated to ensure that the Nafion resin contained in the proton exchange membrane and the catalyst layer contains sufficient water to ensure sufficient conductivity. After the working conditions are stable, the battery is controlled at different discharge currents or voltages. After the test is completed, the experimental data is exported.
[0141] The fuel cell consists of a membrane electrode, a plate, a sealing gasket and an end plate. The plate is made of an airtight hard graphite plate with a size of 50×50×3mm, and the inner side is designed as a parallel serpentine three-flow channel; the sealing gasket is made of ordinary plastic gasket; and the end plate is made of stainless steel plate. The components are tightly assembled to reduce the internal resistance of the battery. The effective area of the membrane electrode in the homemade single cell is 25cm 2 The effective area of the electrode is 25cm 2 After the membrane electrode is installed in the single experimental cell, the single cell performance test is carried out on the test bench. In the electrochemical performance test conditions of the membrane electrode, the humidity of hydrogen and oxygen is 50% RH, the hydrogen pressure and oxygen pressure are adjusted to 0.28MPa and 0.30MPa respectively, the single cell is connected to an external constant current and constant voltage power supply, the battery temperature is raised to 80℃, and the polarization curve and electrochemical impedance curve of the battery are measured.
[0142] After testing, we found Figure 2 The membrane electrode polarization curve comparison diagram of Example 1 and Comparative Examples 1-4 shown in FIG. Figure 3 The shown diagram is a comparison of the electrochemical impedance of the membrane electrodes of Example 1 and Comparative Examples 1-4.
[0143] right Figure 1 and Figure 2 From the analysis, it can be known that compared with the comparative examples 1-4, the membrane electrode performance of Example 1 is obviously superior, and the ohmic impedance is significantly smaller. This is mainly because the L-CNTs, S-CNTs and Pt / C catalyst in Example 1 match each other to form a good conductive path; in addition, the process of separate dispersion of the slurry optimizes the arrangement of CNTs with different aspect ratios, effectively reducing the ohmic impedance.
[0144] The experimental methods in the above examples and comparative examples, unless otherwise specified, are conventional methods, and are carried out according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.
[0145] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A method for preparing a fuel cell membrane electrode based on multi-scale carbon nanotubes, characterized in that: The method comprises the following preparation steps: S1: ultrasonically treating a large aspect ratio carbon nanotube (L-CNTs) solution in a water bath to obtain an L-CNTs slurry; placing a small aspect ratio carbon nanotube (S-CNTs) solution in a ball mill for ball milling to obtain an S-CNTs slurry; shearing, dispersing, and cooling a Pt / C catalyst solution to obtain a Pt / C catalyst slurry; S2: mixing L-CNTs slurry, S-CNTs slurry, Pt / C catalyst slurry and stabilizer to obtain a mixed slurry; the mass ratio of the total mass of L-CNTs slurry and S-CNTs slurry to the mass ratio of Pt / C catalyst slurry is (1-4):10, wherein the mass ratio of L-CNTs slurry to S-CNTs slurry is 1:(1-5); S3: Ultrasonic spraying of the mixed slurry, adjusting the nozzle movement speed and the discharge speed, and controlling the anode platinum loading to 0.05-0.15 mg / cm 2 , the cathode platinum loading is 0.3-0.4 mg / cm 2 , obtaining an anode catalyst layer and a cathode catalyst layer; S4: stacking gas diffusion layers on the anode catalyst layer and the cathode catalyst layer respectively, and then hot pressing to finally obtain a fuel cell membrane electrode based on multi-scale carbon nanotubes.
2. The method for preparing a fuel cell membrane electrode based on multi-scale carbon nanotubes according to claim 1, characterized in that: In step S1, the diameter of the L-CNTs is 10-20 nm and the length is 5-30 um; the diameter of the S-CNTs is 10-20 nm and the length is 1-5 um; the platinum content in the Pt / C catalyst is 20%-60%.
3. The method for preparing a fuel cell membrane electrode based on multi-scale carbon nanotubes according to claim 2, characterized in that: In step S1, the method of ultrasonically treating the L-CNTs solution under water bath conditions is as follows: dissolving the L-CNTs in a certain amount of deionized water and mixing them evenly to form an L-CNTs solution with a mass fraction of 1.5%-2.5%, and ultrasonically treating the L-CNTs solution at a water bath temperature of 8-12°C, gradually reducing the ultrasonic power from 500W to 100W, and the ultrasonic treatment time is 45-75min.
4. The method for preparing a fuel cell membrane electrode based on multi-scale carbon nanotubes according to claim 3, characterized in that: The specific steps of gradually reducing the ultrasonic power from 500 W to 100 W are: first ultrasonic treatment at 500 W for 15-25 min, then ultrasonic treatment at 250-350 W for 15-25 min, and finally ultrasonic treatment at 100 W for 15-25 min.
5. The method for preparing a fuel cell membrane electrode based on multi-scale carbon nanotubes according to claim 2, characterized in that: In step S1, a small aspect ratio carbon nanotube (S-CNTs) solution is placed in a ball mill for ball milling treatment by dissolving S-CNTs in a certain amount of deionized water and mixing them evenly to form a S-CNTs solution with a mass fraction of 1.5%-2.5%; the S-CNTs solution is placed in a ball milling jar and ball milled at 200-300 r / min for 110-130 min at 8-12°C.
6. The method for preparing a fuel cell membrane electrode based on multi-scale carbon nanotubes according to claim 2, characterized in that: In step S1, the method for shearing, dispersing and cooling the Pt / C catalyst solution is: dissolving the Pt / C catalyst in a certain amount of deionized water and mixing evenly to obtain a Pt / C catalyst solution with a mass fraction of 1.5%-2.5%; shearing the Pt / C catalyst at 4500-5500 rpm at 8-12°C for 25-35 minutes, and then transferring it to a high-pressure homogenizer for dispersion.
7. The method for preparing a fuel cell membrane electrode based on multi-scale carbon nanotubes according to claim 2, characterized in that: In step S2, the stabilizer is a Nafion solution with a mass percentage of 4%-6%.
8. The method for preparing a fuel cell membrane electrode based on multi-scale carbon nanotubes according to claim 2, characterized in that: In step S2, the ratio of the dry weight of the stabilizer to the total weight of L-CNTs, S-CNTs and Pt / C catalyst is (0.7-0.9):
1.
9. The method for preparing a fuel cell membrane electrode based on multi-scale carbon nanotubes according to claim 2, characterized in that: In step S2, the specific method of mixing L-CNTs slurry, S-CNTs slurry, Pt / C catalyst slurry and stabilizer is: ultrasonically mix the four at 150-250W for 10-20min at 8-12°C, and then shear at 4500-5500rpm for 25-35min.
10. The method for preparing a fuel cell membrane electrode based on multi-scale carbon nanotubes according to claim 2, characterized in that: In step S4, the thickness of the gas diffusion layer is 215-225 um.
